Strategi Komunikasi Divisi General Affair PT The UNV Serang dalam Mengelola Hubungan Kerja dengan Tenaga Outsourcing - Ahmad Firmansyah; Achmad Nashrudin Priatna; Noerma Kurnia Fajarwati; April Laksana; Putri Handayani (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to describe and analyze the communication strategy of the General Affairs (GA) Division of PT The UNV Serang in managing work relationships with outsourced workers from PT Tri Karya Cemerlang (TKC). Using a qualitative approach and in-depth interview methods, this study found that the GA Division implemented a structured and effective communication strategy, reflecting a deep understanding of Communication Strategy Theory, Organizational Communication, and Communication Management. The strategy involved thorough planning, flexible implementation, and continuous evaluation. The GA Division used various communication channels such as WhatsApp groups, weekly face-to-face meetings, and the use of visual media (photos/videos) to ensure clear and directed communication. This multi-channel approach facilitated timely and accurate information flow between departments and outsourced workers. Additionally, the GA Division positioned itself as a "communication bridge," centralizing coordination for all departments and ensuring smooth operational processes. The communication pattern employed was an effective combination of formal, hierarchical communication and informal, personal communication. This combination served to strengthen relationships, foster mutual understanding, and promote a collaborative work environment. The study highlights the importance of a strategic and adaptable communication framework that ensures seamless coordination, promotes positive work relationships, and contributes to organizational success. This research can serve as a reference for improving communication strategies in similar organizational settings.